INTEGRATION OF MEDICAL CURRICULUM, A NEED OR THREAT? - Muhammad Saeed (Journal of University Medical & Dental College, 2020)
While attending a national Conference on medical curriculum at Islamabad, I witnessed amongst the participants, a sense of being compelled by powerful foreign regulatory bodies to modify present medical curriculum and adopt an integrated medical curriculum in its place. It was being told that our medical graduates, will not be able to get training slots/ residencies in UK /USA after five years if not trained through an integrated medical curriculum